The Effect Of Using English Cartoon Movie On The Seventh Grade Students’ Vocabulary Mastery - Zulty Anika Putri (Indonesian Journal of Education Research (IJoER), 2020)
Purpose of the study: The research aimed to investigate the effect of using English cartoon movie on the seventh grade students’ vocabulary mastery at SMP Negeri 01 Kabupaten Tebo. Methodology: This design of research was quasi-experimental research design which involved two classes, grouped into experimental class (n=24) and control class (n=24). To know the effect of using English cartoon movie on students’ vocabulary mastery, there were three steps in collecting the data; they were pretest, treatment and post-test. Main Findings: The result of post-test in experimental class showed that the mean score was 86.88. Meanwhile, the mean score in control class was 77.08. The difference of mean score of both classes was 9.8. From those results, the researcher found that the class taught with using English cartoon movie performed better than the class taught without using English cartoon movie. Furthermore, the analysis of t-test result showed t-test Sig. 2-tailed (.000) was lower than t-table (.05) (.000 < .05). So, the result of this study was there was a significant effect of using English cartoon movie on the seventh grade students’ vocabulary mastery at SMP Negeri 01 Kabupaten Tebo. Novelty/Originality of this study: The teacher have already served them with the meaning of the vocabulary, they were likely to bring dictionary and memorize it. There were no new innovation happened in this class, so the students did not any attention to the vocabulary that been learned.